Ação da acupuntura auricular chinesa sobre a dor crônica em pessoas com distúrbios musculoesqueléticos na coluna vertebral: ensaio clínico randomizado - Moura, Caroline De Castro (2016)
Chronic pain is one of the main complaints of people with disorders related to the musculoskeletal system; it produces negative impact on the quality of their lives, besides economic and social consequences. Thus, integrative and complementary practices have been used, highlighting auricular acupuncture, in order to reduce chronic painful experience. This intervention consists of an acupuncture therapy technique that works stimulating specific reflex points in the ear, relieving signs and symptoms of various diseases, among them pain. Therefore, the aim of this study was to evaluate the effect of Chinese auricular acupuncture on chronic pain in people with musculoskeletal disorders in the spine. This is a randomized clinical trial held between June 2015 and March 2016. The final sample consisted of 110 people with chronic pain in the spine, for at least three months, registered on the waiting list of the physical therapy clinic and server’s integrated assistance center at UNIFAL-MG. After the initial evaluation, the participants were divided into three groups through randomization: A treated group (n = 37), which received 05 auricular acupuncture sessions based on the precepts of Traditional Chinese Medicine; a placebo group (n = 36) who underwent auricular acupuncture with stimulation points that did not have any connection with the observation focus; and a control group (n = 37) who did not receive the intervention headset. A trained professional evaluated all participants, in three stages: first (before any intervention); a week after the last session of auricular acupuncture, and 15 days after the second evaluation (follow up). The subject characterization instrument, Brief Pain Inventory, and Roland Morris Disability Questionnaire were used, besides the nociceptive threshold in front of mechanical stimulation’s assessment, carried out with the aid of a digital algometry, and tissue temperature evaluation measured by means of a thermo-graphic camera. Data were analyzed with the intention of treating and the statistical analysis was performed through the following tests: Chi-square, Kruskal-Wallis, followed by the Student-Newman Keuls, when necessary; as well as paired McNemar and Wilcoxon. The results showed that pain severity and its interference with daily activities decreased in the treated and placebo groups during the treatment period and remained the same in the follow-up assessment only for the placebo group. Moreover, auricular acupuncture also provided a significant pain relief in these two groups; however, this decreased in the treated group in the follow up evaluation but stayed the same for the placebo group. There was also a reduction in physical disability, for both treated and placebo groups, being more significant for the treated group, and remained the same in the follow up evaluation for both. Furthermore, there was increased tissue temperature between the final and follow-up assessments for both treated and placebo groups. The control group did not show any significant influence for these variables. The nociceptive threshold in front of mechanical stimulation showed no significant variations. Thus, the effect of Chinese auricular acupuncture is clear in behavioral and physiological parameters of chronic pain in the spine.